PERAN ROUNDTABLE ON SUSTAINABLE PALM OIL (RSPO) DALAM PEMBERDAYAAN PEKEBUN SWADAYA KELAPA SAWIT PEREMPUAN DI ROKAN HULU 2021-2022 - Bulki, Voppi Rosea; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The oil palm sector was known as a male-dominated working environment, resulting in the marginalization of women despite their contributions to oil palm cultivation. Women smallholder farmers faced injustices in various aspects, such as low wages, unclear employment status, limited access to resources and land ownership, as well as gender discrimination. This research utilized qualitative research methods, gathering both primary and secondary data. The author conducted interviews with facilitators assisting women smallholder oil palm farmers in Rokan Hulu, and utilized essential documents as additional data sources. Other secondary data were collected through journals, news articles, policies, and relevant written materials. RSPO played a significant role in empowering women through its certification mechanisms. As an NGO, RSPO successfully fulfilled 4 out of 5 roles proposed by Ahmed and Potter. RSPO played a particularly significant role in providing education to the community, namely women smallholder oil palm farmers in Rokan Hulu. Keywords: Equality, Independent Smallholder Farmers, Women, Rokan Hulu, RSPO, Certification